Identification of Cat (Felis catus) Blood Splatter on Cotton Fabric After Periods of Drying Using Leucomalachite Green and Takayama Reagent - Charles, Vanessa Ann; Lestari, Tita Damayanti; Legowo, Djoko; Ismudiono, Ismudiono; Hidajati, Nove; Wahyuni, Retno Sri (Journal of Basic Medical Veterinary, 2021)
Blood-stain or blood splatter analysis when used properly can assist in establishing a chain of events linked to violent crimes (Bevel and Gardner, 2008). The methods used in detecting blood splatters in the field are chemical methods. Leucomalachite green is a colorimetric test which is used to test the presence of blood (Castro and Coyle, 2008). Takayama reagent is a confirmatory test for blood (Strassman, 1922). The aim of this research is to detect the blood splatter on cotton fabric after it has been dried for 1 day, 3 days and 5 days using Leucomalachite green and Takayama reagent. Cotton fabric was specifically chosen for this experiment with 3 different periods of drying. The unstained cotton fabric was cut into squares, and a blood sample was splattered on each piece. The fabrics splattered with blood were then dried for 1 day, 3 days and 5 days. The blood splatter was then tested using Leucomalachite green and Takayama reagent, and the results were noted afterwards. For the control, red food dye was dried for 1 day then tested with Leucomalachite green and Takayama reagent. The image results of the Leucomalachite green test are analyzed using ImageJ software 1.8.0_112 where the red, green and blue pixels are converted to grayscale. The image results of the Takayama test are graded based on the number and pattern of crystal. In conclusion, Leucomalachite green and Takayama reagent are able to detect cat blood splatter on the cotton fabric. Leucomalachite green produced a higher intensity/ darker colour as a result of an older sample, and the lower intensity/ lighter colour as a result of a fresher sample of the Leucomalachite green test. Takayama reagent produced a densely packed pattern of crystals as a result of an older sample, and the loosely packed pattern of crystals as a result of a fresher sample of the Takayama test.